Linkage of administrative family court care proceedings and hospital records for mothers in England: linkage accuracy and cumulative incidence of family court care proceedings after a first live birth - Ireland, Georgina; Wijlaars, Linda; Jay, Matthew; Feng, Qi; Harron, Katie; Grant, Claire; Gilbert, Ruth (International Journal of Population Data Science, 2024)
Introduction Linkage of public law family court care proceedings (CP) data to all women giving birth in NHS hospitals in England allows calculation of the cumulative incidence of CP involvement for mothers with first children born. Objectives To assess linkage accuracy and determine the 10-year cumulative incidence of CP after a first live birth (FLB) for population subgroups. Method NHS England linked records for mothers in Cafcass (Children and Family Court Advisory and Support Service) involved in CP (2007-2021) to all mothers with a delivery in England using Hospital Episode Statistics (HES: 1997-21). We calculated match rates and assessed indirect evidence of potential false positive and missed links. We used survival analyses to estimate cumulative incidence of CP within 10 years overall and for five-year maternal age groups at first live birth. Results Of 120,937 mothers involved in CP, 6.6% (n = 8,010) were excluded due to missing postcode or date of birth, or age < 15 or > 50. Of the remaining 112,927 mothers, 92,891 (82.8%) were linked to a HES delivery record. Match rates were lowest for mothers with an ethnic minority background, older at first case, or residing in Greater London, but improved over time. Of 3,572,737 mothers with a FLB, 38,462 had CP involvement. The cumulative incidence of CP at 10 years from FLB was 1.31% (95% Confidence Interval [CI]; 1.29-1.32) overall and highest in mothers aged 15–19 years (6.79%, 95% CI: 6.69-6.89) and those living in the most deprived areas (2.47%, 95% CI: 2.43-2.51). Conclusion One in 77 of all mothers and one in 15 aged less than 20 at first live birth were involved in CP within 10 years. Linkage error may underestimate the incidence of CP for mothers in London or with an ethnic minority background.